Does better education cause higher income? - Malte Homann; Uwe Jensen (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2013)
While the positive influence of higher education on income has been repeatedly confirmed, the linking channel can be ambiguous. Within the framework of estimating the effect of income on life satisfaction, various sources of endogeneity caused by joint determination are addressed and the earnings equation is reconsidered, too: We cast doubt on the hypothesis of the direct influence of educational achievement on income, using two separate cross-section datasets for full-time employed, male white- or blue-collar workers from German SOEP data. Our data rather suggest that the socio-economic rank of an occupation serves as a factor which links educational achievement and income. One explanation relates to the signaling theory by Spence, another possible explanation is yielded by the existence of a regime of regulations in Germany that require certain formal quali cations to obtain highly-prestigious jobs which are, in general, also better paid.
Keywords: 330